Headache attributed to spontaneous intracranial hypotension and associated possible causes - Valença, Marcelo Moraes (Headache Medicine, 2023)
Bem Junior and coworkers published a very interesting and opportunely case report on spontaneous intracranial hypotension, associated with cerebrospinal fluid (CSF) fistula in this issue. In recent decades, many publications have been addressing the subject. Spontaneous intracranial hypotension is little known among physicians, and the diagnosis is difficult even considering neurologists. Many patients progress without the correct diagnosis for weeks or even months. The clinical expression is classically similar to that found in post-dural puncture headache syndrome, an entity prevalent after spinal anesthesia. The most frequent symptom presentation is orthostatic headache, which worsens in the upright position and subsides after lying down.